Analysis Of The Influence Of Organizational Trust, Psychological Safety And Learning Organization Culture On The Knowledge Sharing Behavior Of Educators In Higher Education - Citra Siwi Hanayanti; Firman Aziz; Susatyo Adhi Pramono; Iwan Henri Kusnadi; Ipah Siti Chuzaipah; Dina Agnesia Sihombing (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The practice of knowledge sharing functions as an essential component which enhances academic collaboration and learning outcomes for universities. The study investigates how organizational trust and psychological safety together with learning organizational culture affect educators' knowledge sharing activities. The investigators applied a quantitative research method by using an explanatory research design to conduct their study. The researchers conducted a survey with 150 lecturers who were selected through purposive sampling methods. The researchers used multiple linear regression analysis after they completed the study instruments validation process and confirmed their reliability and tested the classical assumptions. The study results showed that organizational trust and psychological safety together with learning organizational culture positively and significantly affected knowledge sharing behavior. The research findings demonstrate that organizations can improve their knowledge sharing capabilities through establishing organizational trust and psychological safety systems while developing learning organizational culture frameworks. The study provides theoretical advancements which benefit knowledge management research while delivering practical human resource management solutions for higher education institutions.